2012
DOI: 10.1159/000336208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postoperative Diclofenac on Anastomotic Healing, Skin Wounds and Subcutaneous Collagen Accumulation: A Randomized, Blinded, Placebo-Controlled, Experimental Study

Abstract: Background: Retrospective studies have drawn attention to possible detrimental effects of non-steroidal anti-inflammatory drugs (NSAIDs) on the anastomotic leakage rate after colorectal resection. In this study, we examined the effects of the NSAID diclofenac on the breaking strength of an experimental colonic anastomosis and a skin incision as well as subcutaneous collagen accumulation. Methods: This was a randomized, blinded, placebo-controlled experimental study in 60 male Wistar rats treated with diclofena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
(48 reference statements)
1
22
0
Order By: Relevance
“…NSAIDs, yet distal colonic anastomoses show no detrimental effects 29 . Furthermore, looking at the two studies which found no increased risk of leakage following NSAID administration, both examined distal colonic anastomoses exclusively 27,28 . Their negative findings fall in line with the location dependent findings of other studies, and cannot be generalized to state that there is no association between NSAID use and anastomotic leakage elsewhere in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs, yet distal colonic anastomoses show no detrimental effects 29 . Furthermore, looking at the two studies which found no increased risk of leakage following NSAID administration, both examined distal colonic anastomoses exclusively 27,28 . Their negative findings fall in line with the location dependent findings of other studies, and cannot be generalized to state that there is no association between NSAID use and anastomotic leakage elsewhere in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, diclofenac use has been associated with reductions in anastomotic tensile strength, bursting pressure, and hydroxyproline deposition. 2224 …”
Section: Discussionmentioning
confidence: 99%
“…These clinical findings are supported by animal studies that have demonstrated that NSAID use following bowel anastomosis may be associated with decreased anastomotic strength and increased leak rates 7 8. NSAIDs are implicated in reducing collagen synthesis and hydroxyproline deposition during the healing process.…”
Section: Introductionmentioning
confidence: 76%